Comparison of chlorhexidine–isopropanol with isopropanol skin antisepsis for prevention of surgical‐site infection after abdominal surgery. Issue 7 (30th March 2018) - Harnoss, J. C.; Assadian, O.; Kramer, A.; Probst, P.; Müller‐Lantzsch, C.; Scheerer, L.; Bruckner, T.; Diener, M. K.; Büchler, M. W.; Ulrich, A. B.
Abstract : Background: Prevention of surgical‐site infection (SSI) has received increasing attention. Clinical trials have focused on the role of skin antisepsis in preventing SSI. The benefit of combining antiseptic chlorhexidine with alcohol has not been compared with alcohol‐based skin preparation alone in a prospective controlled clinical trial. Methods: Between August and October 2014, patients undergoing abdominal surgery received preoperative skin antisepsis with 70 per cent isopropanol (PA). Those treated between November 2014 and January 2015 received 2 per cent chlorhexidine with 70 per cent isopropanol (CA). The primary endpoint was SSI on postoperative day (POD) 10, which was evaluated using univariable analysis, and a multivariable logistic regression model correcting for known independent risk factors for SSI. The study protocol was published in the German Registry of Clinical Studies (DRKS00011174). Results: In total, 500 patients undergoing elective midline laparotomy were included (CA 221, PA 279). The incidence of superficial and deep SSIs was significantly different on POD 10: 14 of 212 (6·6 per cent) among those treated with CA and 32 of 260 (12·3 per cent) in those who received PA ( P  = 0·038). In the multivariable analysis, skin antisepsis with CA was an independent factor for reduced incidence of SSI on POD 10 ( P  = 0·034). Conclusion: This study showed a benefit of adding chlorhexidine to alcohol for skin antisepsis in reducing early SSI compared with alcohol alone. Abstract : Chlorhexidine better